(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article provides information about some plants belonging to the flora of Surkhan found in the works of Abu Ali ibn Sina, in particular, about the medicinal plant - Hippophae rhamnoides L. Its botanical description, distribution area, bioecological and medicinal properties are discussed. The presence of beta-carotene (provitamin A) in chakanda helps the development of the human embryo, the pregnancy goes well, and the general condition and growth of the person is at a good level. Small amounts are also used against infectious diseases. After heavy surgical operations, it quickly repairs wounds, makes blood vessels elastic. A sufficient amount of tocopherol makes the heart normal. Opinions are given that preventive consumption of retail products helps people to be healthy.